Comercializadora de tilapia roja (oreochromis) en el cantón la maná, provincia de Cotopaxi - Baque Bonilla, Nancy Veronica (2016)
The current research main objective was to conduct a feasibility study for the creation of a small business dedicated to the marketing of red tilapia in La Mana Canton, Cotopaxi province, 2016; Among the methodology bibliographical research was found that allowed to collect theoretical information for technical scientific basis; likewise the field research was used to obtain information from potential consumers and owners of fish farms through surveys; Market research showed that there is a demand for 412,248 pounds and an offer of 102,000 pounds of red tilapia annually; determining an unmet demand for 310,248 pounds for 2016; This allowed us to know that there is a market segment to capture. The technical study of the proposal showed in detail the size of the project, the plant layout, location and the process of commercialization of tilapia, live, butchered and filleted by flowcharts; plus a description of the machinery, supplies and essential tools for running microenterprise tilapia Deli-called "BQ".